The Development of e-Appointment System for UTHM Health Centre using Laravel Framework - Mohd Ridoi, Siti NurFalahah; Mohd Zin, Dr. Nur Ariffin (Applied Information Technology And Computer Science, 2024)
In response to the challenges posed by conventional appointment management in healthcare, this thesis introduces the ’e-Appointment System for UTHM Health Centre.’ Focused on enhancing accessibility and efficiency, the study employs the prototyping software development model. The system comprises seven modules, addressing user registration, appointment scheduling, real-time availability management, automated notifications, booking records, feedback and ratings, and an administrator dashboard. The research aims to create a user-centric system that aligns with contemporary student expectations. Project planning and a commitment to efficiency underscore the development, contributing to healthcare technology and software knowledge. The abstract thus presents a solution to healthcare management challenges, ensuring students receive optimal care in their academic pursuits.